P0603INFLUENCE OF FERRITIN VALUES IN THE PORGNOSIS OF ACUTE KIDNEY INJURY. (6th June 2020) - Díez, Pablo; Fernández Ramos, Andres; Muñoz Ramos, Patricia; Sanz Sainz, Marta; Santos Sánchez-Rey, Begoña; Ruano, Pablo; Quiroga, Borja
Abstract: Background and Aims: Acute Kidney Injury (AKI) is one of the most frequent causes of hospitalization and many factors have been associated to its prognosis and recovery. The role of iron in AKI physiopathology and its influence is not well known. Recent studies have shown that elevated levels of catalytic iron are associated with higher mortality in patients with AKI, however, catalytic iron is not available in usual clinical practice. Ferritin, especially abundant in the liver, is the primary intracellular iron storage protein. A small amount is secreted to the circulation and is an indirect marker of total body iron deposits. In this study we analyze the influence of iron, with ferritin values, in the prognosis of AKI. Method: We developed a retrospective, single-center study that enrolled patients with AKI, hospitalized in our center between 2013 and 2014 with iron metabolism values in the first 72 hours after admission. At baseline, we collected demographic information, comorbidities, reason for admission and iron metabolism values (ferritin, transferrin, transferrin saturation index and serum iron). We analyzed variables associated with low and high ferritin values and its impact in AKI long-term prognosis using univariate and multivariable Cox regression. Results: Of the 1731 analyzed patients, 833 (48.1%) had ferritin records. The mean age was 78±14 years and 48% of the patients were women. The most frequent comorbidity was hypertension (76%), followed by chronic kidney disease (46%), dyslipidemia (44%), heart failure (31%), diabetes mellitus (29%) and atrial fibrillation (27%). The most frequent reason for admission was infection (35%) followed by AKI (19%). Ferritin values differed significantly according age (p<0.0001), sex (p=0.024), diabetes (0.012), hypertension (p=0.002), neoplasia (p=0.016), reason for admission (p=0.018), baseline CKD-EPI (0.012) and lactate at admission (p<0.0001). During the hospitalization, 165 (20%) patients died. Factor associated to mortality were ferritin>500 ng/ml (p=0.013), lactate at admission (p<0.001), age (p=0.045), hypertension (p=0.014), dyslipidemia (p<0.001), ischemic heart disease (p=0.006), chronic kidney disease (p=0.001), baseline CKD-EPI (p=0.01), atrial fibrillation (p=0.005), neoplasia (p=0.023), Barthel index (p<0.001) and hemoglobin (p=0.006) and bicarbonate (p=0.012) at admission. Multivariate logistic regression demonstrated that ferritin levels over 500 ng/mL was an independent predictor of mortality (1.6 [1, 1-2, 3] HR [CI 95%]) (p=0.013). Conclusion: Ferritin values higher than 500 ng/mL independently predicts mortality in patients admitted with AKI.